ANTIBACTERIAL ACTIVITY TEST OF ETHANOL EXTRACT OF WHITE AND RED FLESH FROM GUAVA LEAF ( Psidium guajava. L) AGAINTS Staphylococcus aureus AND Escherichia coli - Hilda Maysarah; Rika Apriani; Misrahanum Misrahanum (Universitas Syiah Kuala, 2016)
An antibacterial activity test of ethanol extract of white and red flesh from guava leaf (Psidium guajava. L) against S.aureus and E.coli; using agar diffusion method was carried out in order to produce the extract. The extract was collected using maceration method. The concentration of extract was 7,8125; 6,1035; 5,00; 4,8828; 4,3944; and 3,90625 mg/mL. The results showed that both of extracts had antibacterial activities. Ethanol extract of white flesh of fruit guava leaf had (Minimum Inhibitory Concentration) MIC value at 5.000 mg/mL against S.aureus and 4.8828 mg/mL against E.coli. Whereas ethanol extract of red flesh of fruit guava leaf had MIC value at 4.3944 mg/mL against S.aureus and E.coli. MIC value of ethanol extract of white flesh of fruit guava leaf is equal with MIC value of clindamicin concentration at 3.00 µg/mL against S.aureus, and 1.00 µg/mL against E.coli. The MIC value of red flesh of fruit guava leaf is equal to the MIC value of clindamicin concentration at 3.00 µg/mL against S.aureus, and 1.00 µg/mL against E.coli.